PENERAPAN MODEL PEMBELAJARAN WINDOW SHOPPING UNTUK PENINGKATAN KERJASAMA DAN PRESTASI BELAJAR - Hafiza Nafi’ah (DIADIK, 2024)
This study aims to describe collaboration, student achievement, and the effectiveness of the application of the Windows Shopping learning model to improve student achievement in science subjects in class VIII SMP N 1 Gumay Talang. The research method used is Classroom Action Research (CAR) and quasi-experimental. The subjects of this study were grade VIII students of SMP Negeri 1 Gumay Talang in the first semester of the 2022/2023 academic year. The number of students for the CAR class is 26 people, for the experimental class there are 27 people, and for the control class there are 27 people. The data collection method in this study used the Window Shopping learning model observation sheet, cooperation observation sheet, and learning outcomes test. Analysis of the data using the analysis of the average score and tests consisting of a difference test between cycles and a different test of two unrelated samples. The results of the study indicate that the application of the Window Shopping learning model can increase collaboration, learning achievement and effectively improve student learning outcomes in science subjects for class VIII SMP Negeri 1 Gumay Talang